Business trunking solution for IP PBX technology in IP multimedia subsystem (IMS) network architecture / Alif Amir Mohd Sholeh - Mohd Sholeh, Alif Amir (2016)
The development of telecommunications networks is driven by both the needs of CT network carriers to expand and evolve and by the growing challenges posed by IT players. To address these needs and challenges, network carriers are hungry for a new generation of telecommunications core network. The IP Multimedia Subsystem (IMS)standard defines a generic architecture for offering Voice over IP (VoIP) and multimedia services. The private branch exchange (PBX), also called the private automatic branch exchange (PABX), is a dedicated exchange that provides call center functions or hotline functions for enterprises, companies, and banks, and provides special service console functions for fire services and police services. As the network evolves, the concept of the PBX is widened. PBX system needs to register to IMS network in order a user to use it service such as voice call. But in the market, there are two type of IPPBX supporting and not supporting registration with the IMS domain. This paper will discuss these registrations problem and all solutions to overcome it also how the registration works and the complete signaling call flow.